Lung Ultrasound versus Chest X-Ray for the Detection of Fluid Overload in Critically Ill Children: A Systematic Review - Schapka, Emily; Gee, Jerica; Cyrus, John W.; Goldstein, Gregory; Greenfield, Kara; Marinello, Mark; Karam, Oliver (Journal of Pediatric Intensive Care, 2021)
Fluid overload is a common complication of critical illness, associated with increased morbidity and mortality. Pulmonary fluid status is difficult to evaluate clinically and many clinicians utilize chest X-ray (CXR) to identify fluid overload. Adult data have shown lung ultrasound (LUS) to be a more sensitive modality. Our objective was to determine the performance of LUS for detecting fluid overload, with comparison to CXR, in critically ill children. We conducted a systematic review using multiple electronic databases and included studies from inception to November 15, 2020. The sensitivity and specificity of each test were evaluated. Out of 1,209 studies screened, 4 met eligibility criteria. Overall, CXR is reported to have low sensitivity (44–58%) and moderate specificity (52–94%) to detect fluid overload, while LUS is reported to have high sensitivity (90–100%) and specificity (94–100%). Overall, the quality of evidence was moderate, and the gold standard was different in each study. Our systematic review suggests LUS is more sensitive and specific than CXR to identify pulmonary fluid overload in critically ill children. Considering the clinical burden of fluid overload and the relative ease of obtaining LUS, further evaluation of LUS to diagnose volume overload is warranted.
Keywords: child; critical illness; X-rays; ultrasonography; lung; radiography; fluid overload